Initial report of near‐infrared fluorescence imaging as an intraoperative adjunct for lymph node harvesting during robot‐assisted laparoscopic gastrectomy. Issue 7 (29th March 2016) - Herrera‐Almario, Gabriel; Patane, Michael; Sarkaria, Inderpal; Strong, Vivian E.
Abstract : Introduction: Adequate lymphadenectomy is a fundamental aspect of oncologically sound gastrectomies. Robot‐assisted laparoscopic gastrectomy is a minimally invasive alternative that allows functional imaging to be easily integrated to the surgical field and may aid in intraoperative identification of lymphovascular bundles. Methods: Indocyanine green application and near‐infrared fluorescence imaging were used during robot‐assisted laparoscopic gastrectomy as an adjunct for the identification of relevant lymph node basins in real time. Results: A total of 31 patients were included. Twenty‐nine gastrectomies were performed for adenocarcinoma and two wedge resections for neuroendocrine tumors. The mean lymph node retrieval was twenty‐nine (range 17–61) for adenocarcinoma and five for neuroendocrine tumors. In all cases, at least five lymph nodes were seen along the main nodal basins, which provided real time intraoperative feedback regarding lymph node identification. Average time for indocyanine green application and functional imaging was less than 10 min. Conclusions: Near‐infrared fluorescent imaging may provide an improved method to help visualize lymph nodes intraoperatively during robot‐assisted laparoscopic gastrectomy, thus adding a potentially valuable adjunct for lymphadenectomy and overall lymph node retrieval. J. Surg. Oncol. 2016;113:768–770 . © 2016 Wiley Periodicals, Inc.